Mediation and the police: Characteristics of complainants and mediation selection within a civilian police oversight agency in New York - Williams, Cynthia-Lee (Mediation Theory and Practice, 2020)
Currently, few studies have examined mediation programmes within independent police oversight agencies. Moreover, analyses of these programmes primarily focus on the degree of citizen satisfaction. This study adds to the existing research by examining possible characteristics linked to mediation selection within independent police oversight agencies. Specifically, this study considers the long-standing tension experienced between the police and certain groups (e.g. minorities, youths and residents of disadvantaged communities) and attempts to determined which groups are more or less likely to meet with officers to resolve police complaints. The data (obtained from the New York City Civilian Complaint Review Board and United States Census of 2010) allow for an analysis of complainant demographic characteristics and neighbourhood characteristics linked to the complainants. Bivariate and multivariate analyses uncovered group differences in mediation selection. Particularly, the results of this study demonstrate that minorities are more likely to select mediation.